Students' attitudes towards peers with autism in Singapore mainstream secondary Schools : effects of direct contact, knowledge and school goal structure - Lee, Randall Zhisheng (Nanyang Technological University, 2021)
Inclusive education has been a growing focus across the world and Singapore is no exception. While progress has been made towards a more inclusive society in Singapore, considerable challenges still remain. In particular, the existing values and views towards individuals with special needs must be changed. Given that the number of students with special needs attending mainstream schools is increasing, it is important for us to understand the perspectives of major stakeholders. Specifically, this study investigated the social inclusion of students with autism spectrum disorder in mainstream secondary schools in Singapore, from the perspectives of typically developing students. The aim of the study was to explore the influence of direct contact, knowledge about autism and school goal structure on Singapore secondary school students’ attitudes towards peers with autism. Sixty-eight students from mainstream secondary schools participated in the study. Participants completed an online questionnaire measuring their attitudes, the frequency of direct contact with a peer who has autism, the quality of their direct contact experiences, their knowledge about autism, and their perceptions of school goal structure. Findings suggest that students’ attitudes are influenced by the quality of direct contact experiences rather than the frequency, as well as their knowledge about autism. This has crucial implications for inclusive education in Singapore moving forward. Further research is necessary to better understand the factors that impact the social inclusion of students with special needs in Singapore mainstream schools.